Redo cardiac surgery in adults - Schaff, Hartzell V.; Svensson, Lars G.; Machiraju, V.R (Springer New York, 2012)
Redo cardiac surgeries are challenging cases with a myriad of influential factors, ranging from the patient's pathology to the whimsy of the previous surgeon. Redo Cardiac Surgery in Adults, 2nd Edition clearly outlines practical approaches, surgical techniques, and management of associated conditions such as perioperative stroke and acute kidney function. It covers the spectrum of redo cardiac operations, including coronary artery bypass, mitral valve repair, reoperation for prosthetic mitral valve endocarditis, aortic arch reoperation, descending and thoracoabdominal aortic reoperation, and reoperations following endovascular aortic repair. All redo cardiac surgeries present a complex array of challenges beyond what the original procedure demands. This book, written by an outstanding group of prominent physicians, will give the reader the knowledge and tools to approach these cases with confidence.